2023
DOI: 10.3389/fnmol.2023.1168948
|View full text |Cite
|
Sign up to set email alerts
|

In vitro methods in autophagy research: Applications in neurodegenerative diseases and mood disorders

Abstract: BackgroundAutophagy is a conserved physiological intracellular mechanism responsible for the degradation and recycling of cytoplasmic constituents (e.g., damaged organelles, and protein aggregates) to maintain cell homeostasis. Aberrant autophagy has been observed in neurodegenerative diseases, including Alzheimer’s Disease (AD), Parkinson’s Disease (PD), Amyotrophic Lateral Sclerosis (ALS), and Huntington’s Disease (HD), and recently aberrant autophagy has been associated with mood disorders, such as depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…[32] New evidence suggests that there are many common pathogenic factors between ALS and depression, such as excessive apoptosis of post-mitotic cells, endocrine-disrupting chemicals (EDCs), changes in brain-derived neurotrophic factor (BDNF) levels in blood and the central nervous system, insulin resistance, and autophagy regulation. [33,34] Moreover, Young CA and others used a multi-attribute study to determine the prevalence of depression in ALS patients and found it to be common, affecting nearly a quarter of the large study population. 71.8% of comorbid depression patients developed it within 3 years of the ALS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[32] New evidence suggests that there are many common pathogenic factors between ALS and depression, such as excessive apoptosis of post-mitotic cells, endocrine-disrupting chemicals (EDCs), changes in brain-derived neurotrophic factor (BDNF) levels in blood and the central nervous system, insulin resistance, and autophagy regulation. [33,34] Moreover, Young CA and others used a multi-attribute study to determine the prevalence of depression in ALS patients and found it to be common, affecting nearly a quarter of the large study population. 71.8% of comorbid depression patients developed it within 3 years of the ALS diagnosis.…”
Section: Discussionmentioning
confidence: 99%